Perlindungan Hukum Terhadap Tenaga Kerja Migran Menurut Hukum Internasional - Matitakapa, Owen Agustio; Tuhulele, Popi; Waas, Armelia Febriyanti (PATTIMURA Law Study Review, 2025)
This research examines international legal protection for Indonesian Migrant Workers (PMI) abroad, focusing on the implementation of the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (Migrant Convention 1990). The research background is based on the increasing complexity of Indonesian migrant worker issues, particularly since the economic crisis. Limited domestic job opportunities have driven an increasing number of Indonesian workers to migrate abroad to improve their quality of life. However, this phenomenon is not without various risks of rights violations, such as exploitation, forced labor, and physical violence experienced by migrant workers. The study aims to analyze the effectiveness of international and national legal frameworks in providing comprehensive protection for Indonesian Migrant Workers. The case study, such as Debby's experience in Malaysia, illustrates the complexity of problems faced by Indonesian Migrant Workers in destination countries. The research methodology employs a juridical-normative approach, examining various international legal instruments, national legislation, and the role of government institutions like the Indonesian Migrant Workers Protection Agency (BP2MI) and the Ministry of Foreign Affairs in providing protection. The results of the study show that the 1990 Migrant Convention provides a comprehensive protection framework for the basic rights of migrant workers and their families as regulated in Articles 8 to 35. This protection includes the right to life, freedom from torture, freedom of expression, freedom of religion, and access to justice and legal aid. At the national level, Indonesia has adopted these protection principles through Law No. 18 of 2017, which provides a legal basis for the protection of Indonesian Migrant Workers (PMI). The protection mechanism can be carried out through bilateral diplomatic channels or by submitting cases to international courts if necessary.